2010
DOI: 10.1371/journal.pone.0012532
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Bcl11b Leads to Chemoresistance Accompanied by G1 Accumulation

Abstract: BackgroundThe expression of BCL11B was reported in T-cells, neurons and keratinocytes. Aberrations of BCL11B locus leading to abnormal gene transcription were identified in human hematological disorders and corresponding animal models. Recently, the elevated levels of Bcl11b protein have been described in a subset of squameous cell carcinoma cases. Despite the rapidly accumulating knowledge concerning Bcl11b biology, the contribution of this protein to normal or transformed cell homeostasis remains open.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Moreover, ectopic expression of BCL11B in the TLX1 + ALL-SIL T-ALL cell line conferred resistance to the topoisomerase IIα poison etoposide. In accord with other investigations [84,102], we found that BCL11B expression was associated with a reduced proliferation rate (unpublished data). Of relevance to our findings, Schmidt and colleagues reported that BCL11B overexpression in TLX1-negative T-ALL cell lines conferred resistance to etoposide-induced death through a mechanism associated with cell cycle delay at the G 1 /S phase [84].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, ectopic expression of BCL11B in the TLX1 + ALL-SIL T-ALL cell line conferred resistance to the topoisomerase IIα poison etoposide. In accord with other investigations [84,102], we found that BCL11B expression was associated with a reduced proliferation rate (unpublished data). Of relevance to our findings, Schmidt and colleagues reported that BCL11B overexpression in TLX1-negative T-ALL cell lines conferred resistance to etoposide-induced death through a mechanism associated with cell cycle delay at the G 1 /S phase [84].…”
Section: Discussionsupporting
confidence: 93%
“…In accord with other investigations [84,102], we found that BCL11B expression was associated with a reduced proliferation rate (unpublished data). Of relevance to our findings, Schmidt and colleagues reported that BCL11B overexpression in TLX1-negative T-ALL cell lines conferred resistance to etoposide-induced death through a mechanism associated with cell cycle delay at the G 1 /S phase [84]. In view of our earlier findings that TLX1 also stimulates G 1 /S progression [24], it will be interesting to determine whether a similar mechanism operates in TLX1 + T-ALL cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A comparison of genome profiles of acute and lymphoma types revealed BCL11B over-expression in the acute form, regardless of the 14q32 gain/amplification, but either low or no levels of this gene’s expression in the lymphomas; these results suggest that acute and lymphoma types are genomically distinct subtypes, which thus may develop tumors via distinct genetic pathways [38]. Apoptosis resistance triggered by BCL11B over-expression was found to be accompanied by chemo-resistance caused by the accumulation of T-ALL cells in the G1 phase [39].…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45] It was shown recently that the expression of BCL11B in T-cell lines resulted in markedly increased apoptosis resistance following treatment with radiomimetic drugs accompanied by a cell cycle delay caused by accumulation of cells at G1. 46 We exam-BCL11B, a novel putative oncogene in AML haematologica | 2014; 99 (5)ined the consequences of Bcl11b overexpression on proliferation and differentiation in a mouse myeloid 32D(GCSF-R) cell line model. The 32D(GCSF-R) cells, expressing fulllength murine Bcl11b cDNA, had a consistently decreased proliferation rate compared to cells expressing the empty vector or to the parental untransfected cells.…”
mentioning
confidence: 99%